Folate Levels in Third Trimester of Pregnancy - Zafar Iqbal, Ghazia Fatima, Faiz Ahmad Faiz, Hira Ghaffar, Sibgha Naz, Tahreem Anwer, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the folate levels in third trimester of pregnancy Study design: Cross-sectional study Place and duration: Conducted at post graduate medical institute, Lahore. Duration was 6 months from June 2022 to December 2022. Methods: Ninety anemic females were selected from the antenatal clinics of different hospitals of Lahore. These incorporated equal numbers of primigravidae and multigravidae and all of them were in the third trimester of pregnancy. They had not taken any hematinic supplements during the pregnancy. Results: Folate deficiency was seen in 44.4% of the primigravidae with peripheral blood macrocytosis and bone marrow megaloblastosis. An association exists between the clinical anemia and the peripheral blood and bone marrow findings with those of serum and red cell folate levels. Conclusion: Folic acid should be included as a routine in hematinic supplements prescribed for pregnant females to protect them from anemia and its consequent complications. Key words: Folate, gestation, trimester, megaloblastic anemia, macocytosis, bone marrow